A multi-criteria decision-making method based on triangular intuitionistic fuzzy preference information. Issue 3 (2nd July 2016) - Wang, Chao-hui; Wang, Jian-qiang
Abstract: The primary goal of this paper is to provide a new approach to multi-criteria decision-making to tackle situations where triangular intuitionistic fuzzy preference relations represent the evaluation values, and the criterion weight information is incompletely known. First, the triangular intuitionistic fuzzy aggregation operator is developed to aggregate criterion values. Subsequently, a mathematical programming model is employed to derive the optimal weights with incomplete weight information. Then, we present the corresponding triangular intuitionistic fuzzy decision-making method by combining the optimal weights. An illustrative example is given, and a comparative analysis is conducted between the proposed approach and other existing methods to demonstrate the effectiveness and feasibility of the developed approach.